Case Report: Glofitamab in the treatment of a patient with central nervous system-involved Burkitt lymphoma - Huang, Yuejiao; Jiang, Jiawen; Lu, Jinfeng; Sun, Chunfeng; Qian, Juan; You, Xuefen; Lin, Zenghua (Frontiers in Oncology, 2026)
Burkitt lymphoma (BL) is a rare and highly aggressive B-cell non-Hodgkin lymphoma. While targeted combination chemotherapy can be effective, it is associated with a high rate of relapsed or refractory disease and a pronounced propensity for central nervous system (CNS) involvement. Currently, novel therapies such as chimeric antigen receptor T-cell (CAR-T) therapy have not demonstrated established efficacy in BL. Given the poor prognosis and the challenge of managing relapsed/refractory BL, the use of bispecific antibodies, specifically glofitamab, as employed in this case, has yielded a favorable therapeutic outcome. This is particularly noteworthy in the present case, given the patient’s documented CNS infiltration. After the failure of first-line treatment in this case, the combination of glofitamab and a Bruton’s tyrosine kinase inhibitor (BTKi) was used for six cycles, which significantly improved the patient’s CNS infiltration and achieved a long remission period. This provides an opportunity to try glofitamab in the treatment of CNS lymphoma, and we look forward to its confirmation in more BL patients.